Augmented reality supporting deaf students in mainstream schools: Two case studies of practical utility of the technology - Ioannou, Andri; Constantinou, Vaso (My University, 2017)
The study suggests a practical use of augmented reality (AR) in supporting Deaf and Hard of Hearing (DHH) students in mainstream schools. The paper presents two case studies. First, we used AR via wearable glasses to support the communication and feedback loop between the instructor and DHH learner during the lesson. Second, we used AR via a typical tablet to support the DHH students in acquiring vocabulary and subsequently, improving their reading-comprehension capabilities. In the first study, although the wearable AR glasses were not stylish enough to be attractive to the DHH adolescent, who felt uncomfortable wearing them in a real classroom setting, she was positive about the potential value of the technology in providing immediate feedback and communication with the educator. In the second study, the experience was positively endorsed by four participating six-graders and their special teacher who thought that AR technology can be a great supporting tool during reading-comprehension of difficult texts. The study demonstrates the utility of AR technology in real world settings, serving the needs of special education students, in this case, those with hearing loss, potentially contributing to more inclusive classroom environments in mainstream schools.
Keywords: Augmented reality; Deaf; Hard of hearing; Inclusive education; Mainstream education; QR codes; Special education; Technology assisted learning; Wearable ar glasses